Exploring trajectories in dietary adequacy of the B vitamins folate, riboflavin, vitamins B6 and B12, with advancing older age: a systematic review - Gillies, N.; Cameron-Smith, D.; Pundir, S.; Wall, C. R.; Milan, A. M. (British journal of nutrition, 2021)
Maintaining nutritional adequacy contributes to successful ageing. B vitamins involved in one-carbon metabolism regulation (folate, riboflavin, vitamins B6 and B12) are critical nutrients contributing to homocysteine and epigenetic regulation. Although cross-sectional B vitamin intake in ageing populations is characterised, longitudinal changes are infrequently reported. This systematic review explores age-related changes in dietary adequacy of folate, riboflavin, vitamins B6 and B12 in community-dwelling older adults (≥65 years at follow-up). Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, databases (MEDLINE, Embase, BIOSIS, CINAHL) were systematically screened, yielding 1579 records; eight studies were included (n 3119 participants, 2–25 years of follow-up). Quality assessment (modified Newcastle–Ottawa quality scale) rated all of moderate–high quality. The estimated average requirement cut-point method estimated the baseline and follow-up population prevalence of dietary inadequacy. Riboflavin (seven studies, n 1953) inadequacy progressively increased with age; the prevalence of inadequacy increased from baseline by up to 22·6 and 9·3 % in males and females, respectively. Dietary folate adequacy (three studies, n 2321) improved in two studies (by up to 22·4 %), but the third showed increasing (8·1 %) inadequacy. Evidence was similarly limited (two studies, respectively) and inconsistent for vitamins B6 (n 559; −9·9 to 47·9 %) and B12 (n 1410; −4·6 to 7·2 %). This review emphasises the scarcity of evidence regarding micronutrient intake changes with age, highlighting the demand for improved reporting of longitudinal changes in nutrient intake that can better direct micronutrient recommendations for older adults. This review was registered with PROSPERO (CRD42018104364).